Street food in the Historic Center of Cartagena, Colombia: consumers, practices and perceptions (Research, Society and Development, 2021)
Street food is a worldwide phenomenon, with a lack of studies on consumers being noted. Thus, this study sought to characterize consumption practices and hygiene and risks perception among street food consumers in the Historic Center of Cartagena, Colombia. A cross-sectional study was carried out, with the administration of a questionnaire, along with 90 consumers. In the sample, there was a predominance of men (70%), aged up to 24 years (32.2%), with complete higher education (46.6%). For 70%, the consumption of street food occurred from childhood; 57.7% acquired it at least weekly, revealing the habit. The main reasons for purchase were easy access (41.1%) and taste/pleasure (38.3%), with higher probability of consumption (0.929) by women with less education. Fried foods (51.1%) and fruits (26.6%) were the most consumed foods - there was a higher probability of fried foods by women, under 24 years old, with low income (0.8733), and of fruit consumption by men, older than 60 years (0.8502). For 94.4%, street food could offer health risks; 52% trust “sometimes” in the quality and hygiene of the fruit. For 81%, the sale of street food generated work and income. The study reveals the food and social importance of the sector, which demands public attention for its better functioning.